Edukasi Pengenalan Huruf Hijaiyah dengan Memanfaatkan Teknologi Augmented Reality - Fajar Septian; Bobi Agustian (Teknik Informatika Universitas Pamulang, 2020)
Augmented Reality (AR) technology provides opportunities for science and engineering. AR also has great opportunities in the world of education, which is to provide and display additional information in the form of 3D objects, video, sound, and text on an object. Smartphone software developers have developed Augmented reality technology that was previously developed on PC devices where this technology utilizes the existing camera on a smartphone. With this situation, AR technology has the opportunity to be used in the development of a media for recognizing hijaiyah letters, so that children will be happier learning because of its attractive appearance and teachers or parents can more easily teach lessons to their children. The way to use it is as follows: first, the user puts a registered and printed marker, second, the smartphone camera identifies (tracking) the marker. If the marker is invalid, the user repeats the identification process. If the marker is valid and identified, the marker will display the hijaiyah letter object in three-dimensional form. Third, users can understand the shape and pronunciation of hijaiyah letters by touching the virtual button on the marker